2020
DOI: 10.3389/fmed.2020.00517
|View full text |Cite
|
Sign up to set email alerts
|

Personalizing Treatment in IBD: Hype or Reality in 2020? Can We Predict Response to Anti-TNF?

Abstract: The advent of anti-TNF agents as the first approved targeted therapy in the treatment of inflammatory bowel disease (IBD) patients has made a major impact on our existing therapeutic algorithms. They have not only been approved for induction and maintenance treatment in IBD patients, but have also enabled us to define and achieve novel therapeutic outcomes, such as combination of clinical symptom control and endoscopic remission, as well as mucosal healing. Nevertheless, approximately one third of treated pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 153 publications
(183 reference statements)
0
61
1
1
Order By: Relevance
“…Clinical practice will also answer the important question whether patients will still benefit from anti-IL23p19 antagonism if they have previously failed to benefit from anti-IL12p40 antibody therapy, and vice versa ( 114 ). Even with the upcoming availability of p19 inhibitors in addition to the already available anti-p40 antibody, there is still the currently unmet clinical need to establish predictive markers of response to identify the subgroup of IBD patients that have a heightened probability of response to respective treatments ( 115 ). In IL23p19 inhibitors, there has so far been only a report that indicated that higher serum IL22 concentrations were associated with a greater likelihood of response to brazikumab ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical practice will also answer the important question whether patients will still benefit from anti-IL23p19 antagonism if they have previously failed to benefit from anti-IL12p40 antibody therapy, and vice versa ( 114 ). Even with the upcoming availability of p19 inhibitors in addition to the already available anti-p40 antibody, there is still the currently unmet clinical need to establish predictive markers of response to identify the subgroup of IBD patients that have a heightened probability of response to respective treatments ( 115 ). In IL23p19 inhibitors, there has so far been only a report that indicated that higher serum IL22 concentrations were associated with a greater likelihood of response to brazikumab ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is a new concept in our field, but many new findings associated to the ability to predict response, relapse and even adverse events by using clinical data and biomarkers will allow us to choose the best drug, for an individual patient at the right time ( 15 , 16 ). Several factors have been linked to the response to TNF blockade in IBD, including clinical factors, pharmacokinetics, biochemical markers, pharmacogenomics, microbiome signatures, metabolic compounds and mucosal markers ( 17 , 18 ). While there are significant advances allowing a better identification of patients more likely to respond to anti-TNFs, including also a more profound understanding of its pharmacokinetics, few studies have investigated predictive factors of therapeutic efficacy to UST that may improve the probability of response and long-term benefit.…”
Section: Introduction: Do We Need Predictive Factors In Crohn's Diseamentioning
confidence: 99%
“…In addition, laboratory biomarkers provide a reproducibly quantifiable tool for the evaluation of disease status and therapeutic efficacy in IBD patients. Therefore, the discovery of reliable biomarkers would be extremely useful in the clinical practice and adds a great help to assess therapeutic efficacy, minimize side-effects, and optimize personalized medicine and strategy for identifying IBD patients who will benefit from anti-TNF therapy [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%